Quantitative evaluation of an outreach case management model of care for urban Aboriginal and Torres Strait Islander adults living with complex chronic disease: a longitudinal study - Deborah A. Askew; Samantha J. Togni; Sonya Egert; Lynne Rogers; Nichola Potter; Noel E. Hayman; Alan Cass; Alex D. H. Brown; Philip J. Schluter (BMC Health Services Research, 2020)
Abstract Background Chronic diseases are the leading contributor to the excess morbidity and mortality burden experienced by Aboriginal and Torres Strait Islander (hereafter, respectfully, Indigenous) people, compared to their non-Indigenous counterparts. The Home-based Outreach case Management of chronic disease Exploratory (HOME) Study provided person-centred, multidisciplinary care for Indigenous people with chronic disease. This model of care, aligned to Indigenous peoples’ conceptions of health and wellbeing, was integrated within an urban Indigenous primary health care service. We aimed to determine the impact of this model of care on participants’ health and wellbeing at 12 months. Methods HOME Study participants were Indigenous, regular patients of the primary health care service, with a diagnosis of at least one chronic disease, and complex health and social care needs. Data were collected directly from participants and from their medical records at baseline, and 3, 6 and 12 months thereafter. Variables included self-rated health status, depression, utilisation of health services, and key clinical outcomes. Participants’ baseline characteristics were described using frequencies and percentages. Generalized estimating equation (GEE) models were employed to evaluate participant attrition and changes in outcome measures over time. Results 60 participants were enrolled into the study and 37 (62%) completed the 12-month assessment. After receiving outreach case management for 12 months, 73% of participants had good, very good or excellent self-rated health status compared with 33% at baseline (p < 0.001) and 19% of participants had depression compared with 44% at baseline (p = 0.03). Significant increases in appointments with allied health professionals (p < 0.001) and medical specialists other than general practitioners (p = 0.001) were observed at 12-months compared with baseline rates. Mean systolic blood pressure decreased over time (p = 0.02), but there were no significant changes in mean HbA1c, body mass index, or diastolic blood pressure. Conclusions The HOME Study model of care was predicated on a holistic conception of health and aimed to address participants’ health and social care needs. The positive changes in self-rated health and rates of depression evinced that this aim was met, and that participants received the necessary care to support and improve their health and wellbeing.